Analysis of fetal heart rate fluctuations in women diagnosed with preeclampsia during the latent phase of labor - Lucero-Orozco, Nancy B.; Reyes-Lagos, José Javier; Ortíz-Pedroza, María del Rocío; Talavera-Peña, Ana Karen; Abarca-Castro, Eric Alonso; Mendieta-Zerón, Hugo; Pliego-Carrillo, Adriana Cristina; Rodríguez-Arce, Jorge; Zúñiga-Avilés, Luis Adrián; Santiago-Fuentes, Laura Mercedes; Ledesma-Ramírez, Claudia Ivette; Peña-Castillo, Miguel Ángel (Frontiers in Physiology, 2024)
Introduction: Fetal heart rate variability (fHRV) is a tool used to investigate the functioning of the fetal autonomic nervous system. Despite the significance of preeclampsia, fHRV during the latent phase of labor has not been extensively studied. This study aimed to evaluate fetal cardiac autonomic activity by using linear and nonlinear indices of fHRV analysis in women diagnosed with preeclampsia without hypertensive treatment during gestation, compared to normotensive women during the latent phase of labor.A cross-sectional and exploratory study was conducted among pregnant women in the latent phase of labor, forming three study groups: normotensive or control (C, 38.8 ± 1.3 weeks of pregnancy, n = 22), preeclampsia with moderate features (P, 37.6 ± 1.4 weeks of pregnancy n = 10), and preeclampsia with severe features (SP, 36.9 ± 1.2 weeks of pregnancy, n = 12). None of the participants received anti-hypertensive treatment during their pregnancy. Linear and nonlinear features of beat-to- beat fHRV, including temporal, frequency, symbolic dynamics, and entropy measures, were analyzed to compare normotensive and preeclamptic groups.Results: Significantly lower values of multiscale entropy (MSE) and short-term complexity index (Ci) were observed in the preeclamptic groups compared to the C group (p < 0.05). Additionally, higher values of SDNN (standard deviation of R-R intervals) and higher values of LF (low frequency) were found in the P group compared to the C group.Our findings indicate that changes in the complexity of fetal heart rate fluctuations may indicate possible disruptions in the autonomic nervous system of fetuses in groups affected by undiagnosed preeclampsia during pregnancy. Reduced complexity and shifts in fetal autonomic cardiac activity could be associated with preeclampsia's pathophysiological mechanisms during the latent phase of labor.